A expansão do ensino superior privado no Brasil e a participação do financiamento estatal (1995-2004) - Lameza, Jacqueline de Oliveira (2006)
This dissertation presents as subject of study the Private Higher Education in Brazil in the period of 1995 to 2004, prioritizing the under-graduation education. The objectives are: To delineate the importance of the role of the State in the Education, to analyze the growth of Private Superior Education in Brazil and analyze the public financing in this education sector. In this sense, it develops a discussion about the role of the State in the Education, the NeoLiberal State, the principles of the present public policies and the participation of the public and private in the higher education system. The Brazilian private higher education is analyzed considering the institutions expansion, the enrollments, the number of vacancies offered, fulfilled and not fulfilled and also the number of teachers according to their degrees. The State participation in the private sector of the higher education system is examined under the point of view of the Educational Credit (CREDUC) and the Student Financing (FIES). The methodological route includes bibliographical research about the role of the State in the Education, the economy and the education, the private higher education in Brazil, and the present Brazilian educational policies; statistical data collection and analysis about the private and public education in the INEP/MEC, IPEA and IBGE Statistical Database. It includes also an analysis regarding the expenditures with higher education in relation to the GIP. The research s results indicate a significant growth in the private higher education system, being the public educational policies important inducer of this process and also the financial aid to the student, which amplifies the access and permanence opportunities in this educational system. In the guise of final considerations we point the recommendations aimed to contribute in a constructive way to the private higher education debate in Brazil